STUDI KOMPARATIF: ALIRAN LINGUISTIK TRADISIONAL DAN LINGUISTIK STRUKTURAL - Insum Malawat (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
This paper purposes to compare about traditional linguistics and structural linguistics concept. This study is based by assumed if traditional linguistics concept is the oldest genre had took the way to modern linguistics study, it was signed by structuralism of Ferdinand de Saussure ideas. The focus of this study is the ideas or basic concepts of prominent figure in traditional and structural linguistics, and language essence and its phenomena. Its result of this study, the writer founded some general principles of traditional and structural linguistics. Traditional linguistics applied Greek and Latin grammar to describe a language. On the other side, structural linguistics described a language based on the unique characters that language. The lenguistics study on that era was started by Plato and Aristoteles ideas. Structuralism was born in 20th century or in 1916. It is the structuralism birth year that signed by publishing of Course de Linguistique Generale book by Ferdinand de Saussure.